L-amino acid transporter 1 overexpression in nonmelanocytic skin tumors: an immunohistochemical study - Azza G.A Farag; Mostafa A Hammam; Wafaa A Shehata; Dalia R Al-Sharaky; Eman R.G Allah (Wolters Kluwer Medknow Publications, 2019)
Background Despite the low mortality rate of nonmelanoma skin cancer, the associated morbidity and cost place them as the fifth most expensive cancer to treat. Therefore, development of novel agent to treat is needed, but before new therapeutic strategy can be advised, knowledge regarding its molecular mechanisms is required. Objective To elucidate the role of L-amino acid transporter 1 (LAT1) in nonmelanoma skin cancer etiopathogenesis through LAT1 immunohistochemical evaluation in basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) lesions compared with controls, and to correlate this expression with the proliferative activity of these tumors (assessed by Ki-67 antigen) and with the clinicopathological parameters of the studied patients. Patients and methods In this case-control study, 16 patients having BCC, 16 SCC cases, and 10 healthy controls were subjected to history taking, clinical examination, and skin biopsies (from BCC and SCC lesions and site matched of controls). Biopsies were stained by LAT1 and Ki-67 immunohistochemical stains. Results LAT1 immunstaining in epidermis revealed significant gradual increase from controls (18.70±24.23) to BCC (32.00±27.04) to SCC (53.64±56.26) (P=0.013). Moreover, tumor islands in both BCC and SCC groups and the control epidermis showed significant stepwise increase of LAT1 H score from controls (18.70±24.23), to BCC (41.33±51.70) and finally SCC cases (79.29±68.55) (P=0.001). However, there was no significant correlations between LAT1 and Ki-67 in all groups. Conclusion LAT1, through its amino acids transporting function, may participate actively in BCC and SCC etiopathogenesis. Moreover, molecular LAT1-targeting agents may be a promising therapeutic approach for BCC and SCC management programs.